Human rights education and peacebuilding : a comparative study - Holland, Tracey; Martin, J. Paul (Milton Park, Abingdon, Oxon : Routledge, Taylor & Francis Group, 2014)
'This book assesses the role of human rights education (HRE) in the peacebuilding field. Today, most governments, international organisations and non-governmental organisations recognise the importance of human rights in peace- and democracy-building activities in post-conflict regions. However, compared with other components of peacebuilding, little attention and funding have been given to the cultivation of human rights knowledge and skills within these populations. Almost nothing has been committed to understanding how HRE is best accomplished in such difficult circumstances. Human Rights Education and Peacebuilding demonstrates the promise of HRE programs to help bring about peace within challenging post-conflict contexts. Each chapter of this book (a) identifies the short and medium term impacts of seven different HRE programs on their respective target groups, and (b) provides an analysis of the peculiar local contextual factors that influenced each program's rationale for human rights education. More specifically, each chapter addresses these critical questions: - How are communities around the world using HRE to help rebuild their lives in the aftermath of an armed conflict? - How does HRE respond local problems and needs? How similar are the human rights impacts in the different projects? - How can we understand the promise and challenges associated with HRE as a component of community peace-building? This book will be of much interest to students of peacebuilding, conflict resolution, human rights education studies and IR in general'--
Introduction -- Mobilizing to change the status of women: a rights education project in Sierra Leone -- Melel Xojobal: addressing the rights of child workers in Chiapas, Mexico -- Education to address violence against women in rural Peru -- Human rights education in a secondary school in a conflict-torn region of Senegal -- Never again: the Master's degree in human rights in Lima, Peru -- Addressing the causes and conflict: human rights educatio in Liberia -- The City of Women in Cartagena, Colombia, a human rights community of practice -- Conclusion: human rights education and peacebuilding: promises challenges, and outcomes.
Includes bibliographical references (pages 113-120) and index.
Keywords: Human rights -- Study and teaching; Peace-building.